2015
DOI: 10.1016/j.pscychresns.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Brain venular pattern by 7T MRI correlates with memory and haemoglobin in sickle cell anaemia

Abstract: Sickle cell anaemia (SCA) is a hereditary hemoglobinopathy characterised by extensive vascular dysfunction that stems from inflammation, thrombosis and occlusion of post-capillary venules. Cognitive impairment is a neurological complication of SCA whose pathogenesis is unknown. We hypothesised that cerebral venular abnormalities are linked to cognitive impairment in SCA. Thus, we employed 7T magnetic resonance imaging (MRI) to examine the association between venular density and cognitive function in homozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
(44 reference statements)
0
29
0
Order By: Relevance
“…The right and left ECN showed significantly reduced active voxels in our study. Chronic pain patients as well as SCD patients have been shown to have poor cognitive performance (Colombatti et al, 2015, Karp et al, 2006, Moriarty et al, 2011, Nes et al, 2009, Novelli et al, 2015, Zou et al, 2011). Delayed evoked potentials and altered cortical sources in SCD subjects have been observed, indicating a disease-specific alteration that may modify neural networks (Colombatti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The right and left ECN showed significantly reduced active voxels in our study. Chronic pain patients as well as SCD patients have been shown to have poor cognitive performance (Colombatti et al, 2015, Karp et al, 2006, Moriarty et al, 2011, Nes et al, 2009, Novelli et al, 2015, Zou et al, 2011). Delayed evoked potentials and altered cortical sources in SCD subjects have been observed, indicating a disease-specific alteration that may modify neural networks (Colombatti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that patients with "severe" SCD may also have a higher burden of cerebrovascular disease not detectable by conventional MRI methods but associated with cognitive impairment. 31 Establishing trajectories of cognitive performance is important to understanding how SCD may impact cognitive function with aging. Differences in cognition between patients with SCD and control groups are apparent at an early age.…”
Section: Discussionmentioning
confidence: 99%
“…These studies had very little overlap in the tests used to measure cognitive function; however, when grouping the tests by functional domain, three main domains were tested: global functioning and/or intelligence quotient (IQ), executive function and/or processing speed, and memory (for a full list of the tests used, see the Appendix). Ages were similar across three of the studies, Vichinsky et al (7), Mackin et al (27), Novelli et al (28), with mean ages near 30 (31.6, 32.0, and 31.0, respectively); the Kulger et al (29) and van der Land et al (30) studies had younger groups of patients with sickle cell anemia with a mean age of near 20 (mean 19.9, range 11–28 and mean 23 years, range 19–25, respectively). Four of the five studies also had chosen a priori brain regions of interest.…”
Section: Resultsmentioning
confidence: 62%
“…The 7T MRI study found more WMH in patients with sickle cell anemia than the van der Land et al (30), study conducted with 3T MRI. Also, using a 7T MRI, Novelli et al (28) found that patients with sickle cell anemia had lower total venular density and a higher proportion of short vessels when compared to African-American controls.…”
Section: Resultsmentioning
confidence: 99%